Manajemen Peningkatan Mutu Pendidikan di SDS Muhammadiyah 02 Medan - Ramadhani, Muhammad Luthfie; Ritonga, Nursyahrul; Malinda, Leni; Irmayani, Ade; Mahanum, Mahanum (LPPPI Publishing, 2025)
This study aims to describe the planning, organization, implementation and supervision of quality improvement of SDS Muhammadiyah 02 Medan. This study uses a descriptive research type with a qualitative approach. The findings in the study are: (1) Planning for improving the quality of education at SDS Muhammadiyah 02 Medan is participatory planning, which involves all parties in the organization through deliberation. (2) Organization of improving the quality of education at SDS Muhammadiyah 02 Medan is a functional organization, implemented by detailing all tasks, work that must be carried out and done by each personnel in the SDS Muhammadiyah 02 Medan organization in terms of achieving goals. (3) Implementation of improving the quality of education at SDS Muhammadiyah 02 Medan by carrying out several stages in improving the quality of education planning and compiling the needs needed, playing an active role in initiating and implementing policies that are made, providing direction and explanations when a program is being implemented and guiding, motivating and evaluating the sustainability of a program. (4) Supervision of improving the quality of education at SDS Muhammadiyah 02 Medan is internal supervision. Internal supervision is supervision carried out by the head of Dikdasmen as the head of the field in the organization itself.